2021
DOI: 10.1108/bepam-08-2020-0147
|View full text |Cite
|
Sign up to set email alerts
|

Dwellers' perception on challenges and motivators of greening existing buildings in Brunei Darussalam

Abstract: PurposeGreening existing buildings (GEB) considerably improves energy efficiency of old buildings, along with other benefits, but it is not widely practiced. As a part of a wider study, this paper aims to evaluate the perception of building dwellers/owners on the challenges and motivators to GEB in Brunei Darussalam.Design/methodology/approachA structured questionnaire survey collected 109 responses from building owners/dwellers. Cronbach's alpha tested the reliability of the data collected. One-sample t-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The remaining 122 responsive responses (as seen in Table 1) were used for analysis. This registered 32% rate of response (122/381), which is more than the average of 30% in most construction management studies [49,50]. So, the rate of response was regarded as acceptable.…”
Section: Data Collection and Potential Respondentsmentioning
confidence: 83%
“…The remaining 122 responsive responses (as seen in Table 1) were used for analysis. This registered 32% rate of response (122/381), which is more than the average of 30% in most construction management studies [49,50]. So, the rate of response was regarded as acceptable.…”
Section: Data Collection and Potential Respondentsmentioning
confidence: 83%
“…The project was decided to be approached through SLR, two questionnaire surveys and one interviewbased survey, to eventually develop a framework for wider practice of GEB. At the beginning, the SLR identified different GEB methods or processes, common green features that can be equipped in existing buildings, suitability of building types for GEB, and three broad groups of motivators and eight broad groups of challenges to GEB [16]. The first of the two planned questionnaire surveys dealt with identifying motivators and challenges to undertake GEB.…”
Section: Methodsmentioning
confidence: 99%
“…Data from this survey is being analyzed. Meanwhile, a case study identified potential savings from GEB and verified the pay-back period of various household electrical appliances that can be replaced through GEB [17], and the theoretical construct of the second questionnaire survey on technology adoption has been conceptualized [18]. The second questionnaire is being drafted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations